2018
DOI: 10.24200/sci.2018.5226.1154
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of the leaching behavior and dissolution kinetics of copper oxide ore in sulfuric acid lixiviant

Abstract: The leaching behavior of an Iranian copper oxide ore in sulphuric acid was investigated in detail to evaluate the influence of various factors, to optimize the dissolution conditions and to determine the kinetics of the leaching. The results indicated that the increase in the leaching time and temperature enhanced the leaching rate of copper. The leaching rate increased up to a certain value with increasing the agitation rate, acid concentration and liquid/solid ratio and with further increment reduced. Agitai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Therefore, it can be concluded that the activation energy (9.8 kJ/mol) of the first leaching stage described the Cu dissolution in hydroxide form with sulfuric acid, following the ash diffusion model. This model was reported previously for the sulfuric acid-assisted Cu leaching from oxide ores containing the Cu 2 (OH) 2 •CO 3 phase [25,26]. However, the obtained activation energy was higher than that of the present work, 20.6 kJ/mol [25], and 26.69 kJ/mol [26].…”
Section: Mechanism Of Cu Leaching From Waste Sludge In Sulfuric Acidsupporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, it can be concluded that the activation energy (9.8 kJ/mol) of the first leaching stage described the Cu dissolution in hydroxide form with sulfuric acid, following the ash diffusion model. This model was reported previously for the sulfuric acid-assisted Cu leaching from oxide ores containing the Cu 2 (OH) 2 •CO 3 phase [25,26]. However, the obtained activation energy was higher than that of the present work, 20.6 kJ/mol [25], and 26.69 kJ/mol [26].…”
Section: Mechanism Of Cu Leaching From Waste Sludge In Sulfuric Acidsupporting
confidence: 79%
“…This model was reported previously for the sulfuric acid-assisted Cu leaching from oxide ores containing the Cu 2 (OH) 2 •CO 3 phase [25,26]. However, the obtained activation energy was higher than that of the present work, 20.6 kJ/mol [25], and 26.69 kJ/mol [26]. The difference was attributed to the higher content of Ca (16.7%) and SiO 2 (37.04 to 69.2%) in the copper ores, compared to that of the copper sludge (Ca 6.24%, SiO 2 0%), the latter being able to precipitate on the surface of the sample particle during leaching.…”
Section: Mechanism Of Cu Leaching From Waste Sludge In Sulfuric Acidsupporting
confidence: 56%
“…The authors claimed that the shrinking core model complies with the obtained leaching kinetic experimental data. Using a 13% sulfuric acid concentration, stirring speed of 600 rpm, liquid/solid ratio of 10 mL/g, and 50 o C as reaction temperature, Azizi et al [17] managed to dissolve about 91% copper content after 80 min leaching time. The dissolution kinetics was examined according to heterogeneous models and found that the dissolution of copper in sulfuric acid solution is controlled by the diffusion through the product layer considering the shrinking core model to be appropriate enough to describe the leaching process.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The average activation energy of copper leaching from low-grade cuprite ores was determined to be 45.28 kJ mol-1 by Bai et al [16]. Azizi et al [17] estimated a value of 26.699 kJ/mole for the dissolution kinetics of copper oxide ore in sulfuric acid. In their study, Tanaydin and Demirkiran [18] reported an activation energy value of 34.69 kJ/mole for the leaching kinetics of malachite in perchloric acid solutions.…”
Section: Effect Of Temperature On Ks and Dmentioning
confidence: 99%
“…Alloys of Copper have the immense capability for usage in a variety of industrial sectors including marine systems, construction, transportation, for encapsulating material wastages especially nuclear wastes etc and this usage is possible mainly because of their 2 superior thermal and electrical conductivities, a unique combination of ductility and strength, exemplary resistance to corrosion etc [1][2][3][4][5] Even though there exists an everlasting demand for the alloys of copper (Cu) in several industrial sectors, the usage of these alloys are restricted due to the difficulty in welding them [6][7][8][9]. Fusion-based joining techniques are not suitable for copper, as the existence of pernicious and eruptive constituents such as zinc (present in the alloys of Cu) and other oxides (adherent in nature) deteriorate the quality of weld [10][11][12][13]. In addition to this, the peculiar characteristic features of alloys of Cu namely, larger level of thermal diffusivity, elevated oxidation rate, etc also hinder the successful welding of alloys of Cu by fusion-based joining techniques [14,15].…”
Section: Introductionmentioning
confidence: 99%